Penguatan Spritual Masyarakat Perumahan Puri Taman Sari Kelurahan Borong melalui Pengajian Lorong (PELOR): Spritual Strengthening of the Puri Taman Sari Residential Community Borong District through Lorong Reaction (PELOR) - Rosmita, Rosmita; Nasaruddin, Nasaruddin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
The Lorong Recitation Activity (PELOR) is presented as a strategic program of the Makassar City Government, namely